On Conjugacy of p-gonal Automorphisms of Riemann Surfaces - Gromadzki, Grzegorz (Revista Matemática Complutense, 2008)
The classical Castelnuovo-Severi theorem implies that for g > (p-1)², a p-gonal automorphism group of a cyclic p-gonal Riemann surface X of genus g is unique. Here we deal with the case g ≤ (p-1)² we give a new and short proof of a result of Gonzalez-Diez that a cyclic p-gonal Riemann surface of such genus has one conjugacy class of p-gonal automorphism groups in the group of automorphisms of X.